“El papel de pared amarillo” y la ansiedad por la autoría femenina - Álvarez Espinoza, Nazira (2016)
Every society develops a series of paradigms to establish human behaviors as a way to exercise control over its individuals and maintain the status quo. These paradigms are an abuse against the female collective through means of different measures such as the imprisonment and isolation of a subject by using female madness as an excuse. In “The Yellow Wallpaper” by Charlotte Perkins Gilman, the protagonist is in an internal and external struggle in order to reclaim her female authorship and thus reaffirm herself against the patriarcal ideology that tries to imprison and classify her as crazy.